Baseline, Trend, and Normalization of Carcinoembryonic Antigen as Prognostic Factors in Epidermal Growth Factor Receptor-Mutant Nonsmall Cell Lung Cancer Patients Treated With First-Line Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors. Issue 50 (December 2015) - Chen, Yu-Mu; Lai, Chien-Hao; Chang, Huang-Chih; Chao, Tung-Ying; Tseng, Chia-Cheng; Fang, Wen-Feng; Wang, Chin-Chou; Chung, Yu-Hsiu; Huang, Kuo-Tung; Chen, Hung-Cheng; Chang, Ya-Chun; Lin, Meng-Chih
Abstract : Abstract: Among epidermal growth factor receptor ( EGFR ) mutation status unknown nonsmall cell lung cancer (NSCLC) patients, those with higher carcinoembryonic antigen (CEA) level are more likely to response to EGFR-tyrosine kinase inhibitors (TKIs) because they tend to have mutant epidermal growth factor receptor ( EGFR ). However, patients with higher CEA also have more tumor burden. With the above paradoxical evidence, it is prudent to understand the prognostic significance of baseline CEA in patients with EGFR -mutant NSCLC treated with first-line EGFR-TKIs. The clinical significance of the trend in CEA after treatment and the impact of CEA normalization during EGFR-TKI therapy are also unknown and potentially important. A total of 241 patients who received first-line EGFR-TKIs were included. As to baseline CEA, patients were divided into normal, low, and high baseline CEA by cut point determined by receiver operating characteristic curves. As to CEA responses, patients were divided into 3 groups accordingly to their amount of CEA change after taking TKIs. In group A, 1-month follow-up CEA level decreased more than 35% with nadir CEA normalization; in group B, 1-month follow-up CEA level decreased more than 35% without nadir CEA normalization; and in group C, 1-month follow-up CEA level decreased less than 35% or increased. Patients with higher baseline CEA levels had shorter progression-free survival (PFS) and overall survival (OS) (CEA > 32 vs 5–32 vs <5 ng/mL, PFS = 8.8 vs 11.3 vs 14.4 months, respectively, P < 0.001; OS = 17.8 vs 22.0 vs 27.9 months, respectively, P = 0.01). For trend and CEA normalization in groups A, B, and C, PFS was 14.3, 10.6, and 7.1 months, respectively ( P < 0.001); OS was 29.7, 20.0, and 16.2 months, respectively ( P < 0.001). Baseline, trend, and normalization of CEA levels are potential prognostic markers for patients with EGFR -mutant advanced NSCLC treated with first line EGFR-TKIs.